2016
DOI: 10.1177/1708538116671235
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to prevent TEVAR-related spinal cord ischemia

Abstract: Spinal cord ischemia remains the Achilles' heel of thoracic and thoracoabdominal diseases management. Great improvements in morbidity and mortality have been obtained with the endovascular approach TEVAR (Thoracic Endovascular Aortic Repair) but this devastating complication continues to severely affect the quality of life, even if the primary success of the procedure - dissection/aneurysm exclusion - has been achieved. Several strategies to deal with this complication have been published in the literature ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 51 publications
0
24
0
Order By: Relevance
“…This is consistent vascular adaptation in increased quantity and density of arterioles and a change of arrangement, parallel to the spinal cord (collateral maturation) to permit flow from the subclavian arteries rostrally and the hypogastric arteries caudally. 9,11,15,16 Furthermore, pig models recovered quickly due to this collateral vascular supply network. 15 Among the 6000 segmental arteries' ligation, there were no cases of paraplegia, so it is inferable that the ischemic event did not take place.…”
Section: Applied Concept Of the Collateral Circulationmentioning
confidence: 92%
See 1 more Smart Citation
“…This is consistent vascular adaptation in increased quantity and density of arterioles and a change of arrangement, parallel to the spinal cord (collateral maturation) to permit flow from the subclavian arteries rostrally and the hypogastric arteries caudally. 9,11,15,16 Furthermore, pig models recovered quickly due to this collateral vascular supply network. 15 Among the 6000 segmental arteries' ligation, there were no cases of paraplegia, so it is inferable that the ischemic event did not take place.…”
Section: Applied Concept Of the Collateral Circulationmentioning
confidence: 92%
“…12,13 Different studies in animals showed that the interruption of the flow of all segments to the spinal cord did not produce hypoxic intrathecal acidosis or spinal dysfunction, which remained until the subclavian or middle sacral artery clamping was done. 11 There is a specific case in which the collateral pathway lacks vascular resistance and the main source decreases its flow, which is called steal; for example, in the event of an aortic cross-clamp, drug-induced arteriovenous shunts, or in the case of bleeding from the intercostal artery in an open excluded aortic segment, conditions demonstrated by experimentation. 9,14 A postmortem study in humans demonstrated the permeability of collateral pathways to the spinal cord by injection of dye.…”
Section: Applied Concept Of the Collateral Circulationmentioning
confidence: 99%
“…Another approach is to suspend drainage postoperatively as soon as the patient is able to demonstrate normal force in the lower limbs, keeping MAP at 90-100 mmHg. If the patient develops symptoms, a neurological evaluation is recommended followed by haemodynamic optimization and CSF drainage increase (if it has been decreased in the meantime) [46].…”
Section: Postoperative Sci Preventionmentioning
confidence: 99%
“…Immediate, proactive, and aggressive strategies may be able to successfully treat SCI as there may be an early window of time in which certain forms of SCI may be reversible [9], but it should be better prevented. A variety of protective strategies have been reported, such as hemodynamic control, drainage of cerebrospinal fluid (CSF), and neuroprotective pharmacotherapeutic agents [6,22,24].…”
Section: Introductionmentioning
confidence: 99%